Revolutionizing Petrology and Mineralogy: The Study of AI and Advanced Sensor Technologies - Kazi Kutubuddin Sayyad Liyakat (International Journal of Minerals, 2025)
Petrology and mineralogy are fundamental to understanding Earth's intricate processes, from crustal evolution to economic resource formation. However, traditional methods, while precise, are often laborious, time-consuming, and occasionally subject to interpretive bias. This abstract explores the transformative potential of integrating cutting-edge Artificial Intelligence (AI) and advanced sensor technologies to revolutionize data acquisition, analysis, and interpretation in these critical geosciences. Advanced sensor technologies, including high-resolution spectral imaging (hyperspectral, Raman), automated X-ray diffraction (XRD), X-ray fluorescence (XRF), scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDS), micro-computed tomography (µCT), and even drone-mounted LiDAR, are generating unprecedented volumes of multi-modal data. These sensors provide rapid, non-destructive, and highly detailed information on mineral composition, crystal structure, textural relationships, and bulk rock chemistry, both in the laboratory and in field settings. AI algorithms, including machine learning (ML), deep learning (DL), and computer vision, are uniquely positioned to process and interpret these vast, complex datasets. These algorithms enable automated mineral identification, precise rock classification, quantitative textural analysis, and the detection of subtle geological patterns and anomalies that might elude human observation. Applications span from automated thin section analysis and mineral liberation analysis to predictive modeling of ore grades, identification of alteration zones, and classification of extraterrestrial materials. The synergy reduces subjectivity, significantly enhances the efficiency and accuracy of geological investigations, and accelerates the discovery pipeline. This integration promises not only to streamline existing workflows but also to unveil previously undetectable relationships within geological systems, pushing the boundaries of scientific inquiry. The future of petrology and mineralogy lies in these intelligent, data-driven approaches, fostering autonomous laboratories, intelligent field mapping systems, and advanced predictive models crucial for sustainable resource exploration, environmental monitoring, and understanding planetary evolution.
Keywords: Machine Learning; Petrology; SEM-EDS; XRD; XRF; artificial intelligence; automated analysis; geosciences; hyperspectral imaging; mineralogy; sensor technology